Safety culture assessing and changing the behaviour of organisations - Taylor, John Bernard (Psychological and behavioral aspects of risk series, 2010)
Following an accident, the lack of a 'good' safety management system, compounded by a 'poor' safety culture, is a charge often laid on organisations. This title highlights examples ranging from the loss of the Titanic, to Bhopal, and the Tokaimura criticality event.